1997
DOI: 10.1177/000992289703600302
|View full text |Cite
|
Sign up to set email alerts
|

Immunizing Preschool Children: Beliefs and Practices of Pediatric Residents

Abstract: Immunization practices and knowledge of vaccine contraindications among pediatric residents were assessed at five pediatric training facilities by surveying 227 pediatric residents. Residents administer vaccines even in the presence of an afebrile minor illness. They are less likely to vaccinate if a fever (<102F) is present. Only 57% of residents report administering vaccines at the 15-month well-child checks. Many residents had difficulty recognizing true and false contraindications, though third-year res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Many studies conducted in United Kingdom and United States of America revealed that, as with practicing physicians, parents and other medical staff possess varying knowledge regarding childhood vaccines [2,3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies conducted in United Kingdom and United States of America revealed that, as with practicing physicians, parents and other medical staff possess varying knowledge regarding childhood vaccines [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Knowledge and practice about children’s vaccines, communication about the risks and benefits of vaccines, disease risks, and other vaccine information should be part of the training curriculum in immunization area [ 1 ]. Many studies conducted in United Kingdom and United States of America revealed that, as with practicing physicians, parents and other medical staff possess varying knowledge regarding childhood vaccines [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One cause of missed opportunities is parental or provider misconceptions about the true contraindications to vaccination. 19,[21][22][23][24][25][26][27][28][29] As was evident from this study, minor illnesses and fever are often erroneously thought to preclude vaccination. Canadian immunization guidelines clearly stipulate that mild illnesses, with or without fever, which include colds and upper respiratory tract infections, are not contraindications to vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…Other potential causes of missed immunization opportunities in appointments kept are overcautious interpretation of immunization contraindications 14,15 and a reluctance to give multiple vaccines. 16,17 At the time of our study, most residents and faculty recommended diphtheria and tetanus toxoids and acellular pertussis vaccine rather than diphtheria and tetanus toxoids and pertussis vaccine, and inactivated poliovirus vaccine rather than oral poliovirus vaccine.…”
Section: Commentmentioning
confidence: 99%